The Impacts of Risk-Management Committee Characteristics and Prestige on Efficiency - Yueh, Cheng Wu; Qian, Long Kweh; Wen-Min, Lu; Noor Azlinna, Azizan (Operational Research Society Ltd., 2016)
We examine the effects of risk-management committee characteristics and prestige on efficiency, as well as the moderating effect of risk-management committee prestige on the association between risk-management committee characteristics and the efficiency of Malaysian insurance companies between 2008 and 2013. We apply the dynamic network slacks-based measure model to estimate efficiency, and truncated regression with a bootstrapping procedure to examine the impacts of risk-management committee characteristics and prestige on efficiency. We find significantly positive relationships among the variables, with the exception of the number of risk-management committee meetings. Furthermore, risk-management committee prestige could minimize the positive effect of risk-management committee characteristics on efficiency.